Yagi-Uda Antenna For L-Band Frequency Range - Sharma, Gulshan; Sharma, Anand N.; Duvey, Ashish; Singhal, P. K. (International Journal of Engineering and Technology, 2012)
A yagi-uda antenna for L-band (1-   2GHz) frequency range is presented. The designing formulas and related antenna characteristics such as return loss, radiation pattern and gain were also discussed in this paper.